STRATEGIC PRIORITIES FOR THE DEVELOPMENT OF THE RUSSIAN ARCTIC AND INSTRUMENTS FOR THEIR RESOURCE SUPPORT - Irina V. Novikova; Murad K. Alimuradov (Север и рынок: формирование экономического порядка)
This study, grounded in the strategizing methodology of Academician V. L. Kvint, emphasizes the necessity of establishing resource support mechanisms for the strategic priorities governing the development of Russia’s Arctic. The primary objective is to assess the potential resource security required to implement these priorities, utilizing the proposed methodological framework. Resource allocation must consider both mobility and accessibility at all stages of strategic execution. The efficient redistribution of limited resources to leverage existing and emerging competitive advantages necessitates the establishment of an effective system for monitoring and controlling the implementation of these priorities. Analyzing official statistical data from 2018–2023, the study evaluates the potential of labor, material, and financial resources to support the Arctic Development Strategy of the Russian Federation through 2035. The analysis encompasses regional trends in key indicators such as population dynamics (natural and migratory growth), workforce metrics (excluding small businesses), average monthly wages, unemployment and informal employment rates, investments in fixed assets, financial inflows, and the proportion of unprofitable businesses. To strengthen resource security, the article proposes upgrading financial tools and mechanisms for providing the working population with Northern benefits. It highlights the potential of digital technologies, artificial intelligence, and remote employment to partially offset the reliance on expensive and scarce labor resources. Financial support for implementing the Arctic development strategy can be bolstered by diversifying funding sources, including digital financing methods, across all stages of execution.